2008
DOI: 10.1111/j.1600-0501.2008.01533.x-i2
|View full text |Cite
|
Sign up to set email alerts
|

Immediate functional loading of TiOblast dental implants in full‐arch edentulous mandibles: a 3‐year prospective study

Abstract: Introduction: Implant‐prosthetic rehabilitation of the completely edentulous mandible has evolved to a simplified procedure with shorter treatment time and survival rates of 95–100% depending on the implant system used. Purpose: The aim was to evaluate the 3‐year clinical success of Astra Tech TiOblast implants, functionally loaded on the day of surgery with a fixed full‐arch bridge in the mandible. Materials and methods: One hundred and twenty‐five implants of 3.5–4 mm width and 11–17 mm length were instal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
82
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(88 citation statements)
references
References 14 publications
6
82
0
Order By: Relevance
“…Taking into account these preliminary considerations, the positive results described in this present study can be attributed to the interaction of several favorable contributing factors: the use of implants with the longest possible lengths, an immediate crossarch splinting of the implants with a passively fitting bar minimizing micromobility, and an even occlusal load distribution on a sufficient number of implants. In our study, each patient received 6 to 8 implants: in the upper jaw, the implants were distributed at sites 3,5,6,8,9,11,12, and 14, whereas in the mandible, they were distributed at sites 19, 21, 23, 26, 28, and 30. Whenever possible, depending on the opposing dentition, the cross-arch implant-supported restoration was given a fully balanced occlusion and articulation with an equal spread of the load to all implants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account these preliminary considerations, the positive results described in this present study can be attributed to the interaction of several favorable contributing factors: the use of implants with the longest possible lengths, an immediate crossarch splinting of the implants with a passively fitting bar minimizing micromobility, and an even occlusal load distribution on a sufficient number of implants. In our study, each patient received 6 to 8 implants: in the upper jaw, the implants were distributed at sites 3,5,6,8,9,11,12, and 14, whereas in the mandible, they were distributed at sites 19, 21, 23, 26, 28, and 30. Whenever possible, depending on the opposing dentition, the cross-arch implant-supported restoration was given a fully balanced occlusion and articulation with an equal spread of the load to all implants.…”
Section: Discussionmentioning
confidence: 99%
“…7 It has been seen that immediate loading reduces functional discomfort and also improves the outcome of the implants, thus avoiding the risk of implant failure due to the unexpected overload imposed on the top of the fixtures in the early healing phase. 8 Survival rates of 96% to 100% are reported for immediately loaded full-arch fixed prosthesis in the mandible. [9][10][11] Few studies have evaluated the success of immediately loaded implants in the edentulous maxilla, but the preliminary results seem encouraging.…”
mentioning
confidence: 96%
“…16,21,22 The more recent short-and medium-term studies have reported invariably higher success rates (90-100%) for immediately loaded implants when combined with fixed prostheses. [23][24][25] These high success rates were attributed to several factors, such as ensuring balanced occlusion and equal distribution of forces between the loaded implants especially when incorporating cantilevers in the prosthesis designs. 17,23,[26][27][28][29] Moreover, in order to reduce surgical morbidity as well as costs of implants (associated both with treatment and posttreatment), there has been increasing interest in the reduction of the number of implants for the support of prostheses.…”
Section: Introductionmentioning
confidence: 97%
“…Indeed, this too has now become an important area of study with several studies focused on the determination of how many fixtures are necessary to provide successful support of their overlying prostheses. 17,21,24,26,30,31 As mentioned above, a number of clinical studies have attempted to investigate the efficacy of the immediate loading concept as a feasible treatment modality. However, most studies had no control groups, to which outcomes of the immediate loading treatment could be compared, thus limiting the validity of the conclusions reached.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon has been the basis for multiple orthopedic and dental rehabilitation procedures, paving the way for quality of life improvement of a large number of patients [6]. The introduction of titanium and its alloys to implant dentistry has marked an era where the main driving force for advances in implant engineering has been centered at decreasing or eliminating the hiatus between surgical placement and functional loading due to improved host-to-implant response [7][8][9][10]. Nonetheless, clinical and basic research on the field of implant dentistry resulted in a lack of sequential and hierarchical approach for implant designing that challenges biomedical engineers to retrospectively address the interaction of the main design parameters such as macrogeometry, microgeometry, nanogeometry, and surgical instrumentation in an objective fashion [11].…”
Section: Introductionmentioning
confidence: 99%